Succinylation-related molecular activities in cancer: metabolic adaptations, immune landscape, and prognostic significance in colorectal cancer - Jiang, Zhihang; Li, Xiaoqing; Hu, Long; Jiang, Zheng (Frontiers in Immunology, 2025)
BackgroundSuccinylation, a key post-translational modification, plays a crucial role in metabolic regulation and tumor progression. However, its influence on the tumor immune microenvironment and its prognostic implications remain unclear. A systematic pan-cancer analysis of succinylation-related molecular activities is needed.MethodsBulk transcriptomic, single-cell RNA sequencing, and spatial transcriptomic data across pan-cancer from TCGA, GEO, TISCH, and multiple other databases were analyzed. Succinylation scores were calculated using Gene Set Variation Analysis (GSVA). The interactions between succinylation scores, immune infiltration, tumor microenvironment, tumor mutational burden, and immunotherapy response were assessed. A succinylation-based prognostic model was constructed and validated in colorectal cancer (CRC) cohorts. PCED1A protein expression was evaluated by immunohistochemistry and Western blotting. The function of PCED1A in CRC was investigated through in vitro experiments.ResultsSuccinylation scores were significantly altered in multiple tumor types. Higher succinylation scores correlated with mitochondrial oxidative phosphorylation, while lower succinylation scores were linked to immune cell differentiation. Spatial transcriptomic analysis showed a negative correlation between succinylation scores and immune cell activity in tumor-adjacent regions. A prognostic model consisting of 11 succinylation-related genes (ATP6V1C2, CAPS, DAPK1, P4HA1, PCED1A, RASL10B, AGT, EREG, HYAL1, SARAF, and SLC4A4) was developed. High-risk patients exhibited significantly shorter overall survival. PCED1A was upregulated in CRC and positively associated with SIRT5. Overexpression of PCED1A promoted intracellular protein desuccinylation, along with enhanced CRC cell proliferation, migration, and invasion.ConclusionOur analysis demonstrates that succinylation-related molecular activities display distinct expression patterns across cancers, which are associated with metabolic regulation, immune modulation, and disease prognosis. The succinylation-based prognostic model provides a novel risk stratification tool for CRC, while PCED1A-dependent succinylation regulation may serve as a potential therapeutic target.